Smart Sanitizer Disperser with Level Monitoring - et. al., Chittaranjan Tadikonda, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A smart sanitizer is an automatic sanitizer dispensing machine with no physical contact. It is an alcohol-based hand sanitizer which can be used in schools, hospitals, work places, offices and much more. In this alcohol is basically a solvent and not only a solvent it is also a very good disinfectant which is very much required in this current pandemic, as alcohol is volatile so it will vaporise instantly after application to hands. It is also proven and well known that above 70% of alcohol can kill Coronavirus in hands. In this we are using IR sensor to sense the hand placed near the bottle, esp32 as microcontroller which sense the distance and the result is the pump running to pump out the hand sanitizer. Ultrasonic sensor for the sensing the level of percentage that present in the bottle, the esp32 will sense the distance and the result is to send the alert when the percent of sanitizer in the bottle is less than the threshold, esp32 has the inbuilt network connectivity like WIFI module or Bluetooth module which is used to transfer the data from the esp32 to cloud. The data from the esp32 is analysed and the required alert are given